2012
DOI: 10.1002/ptr.4820
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity‐guided Isolation of Antiosteoporotic Compounds from Ligustrum lucidum

Abstract: The fruits of Ligustrum lucidum (FLL) has long been used for the treatment of osteoporosis in China, but the antiosteoporotic compounds in FLL are still poorly understood. In this study, the alkaline phosphatase (ALP) activity-guided isolation of osteogenic components from FLL was carried out by using osteoblast-like UMR-106 cells. Eight compounds, namely tyrosol (1), tyrosyl acetate (2), hydroxytyrosol (3), salidroside (4), oleoside dimethyl ester (5), oleoside-7-ethyl-11-methyl ester (6), nuzhenide (7), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…In addition, Zhang et al (Chen et al, 2013) demonstrated that aqueous extract of FLL and its 20% ethanol fraction exhibited estrogenic activity via ERα and ERβ mediated estrogen response element gene expression in Hela cells. Further, Wang et al (2011) found that the addition of ER antagonist (ICI182780) to aqueous extract of FLL treated UMR-106 osteoblasts effectively inhibited ALP activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Zhang et al (Chen et al, 2013) demonstrated that aqueous extract of FLL and its 20% ethanol fraction exhibited estrogenic activity via ERα and ERβ mediated estrogen response element gene expression in Hela cells. Further, Wang et al (2011) found that the addition of ER antagonist (ICI182780) to aqueous extract of FLL treated UMR-106 osteoblasts effectively inhibited ALP activity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Nox4 is widely expressed in bone (Fu et al, 2015) and uteri (Fletcher et al, 2014). Additionally, FLL has been demonstrated to exhibit antioxidant activity in vitro (Chen et al, 2013). Ovariectomy aggravates bone loss partly through disturbing redox homeostasis (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An ethanolic extract of Cuscuta chinensis and water extract of Ligustrum lucidum were prepared as described in previous studies Chen et al, 2012). Dried leaves of Epimedium brevicornum, dried rhizomes of Rhizoma drynariae, and dried roots of Polygonum multiflorum were purchased from Tongrentang Chinese Medicine (Beijing, China) and voucher specimens were deposited in the herbarium of Herpetology and Herbarium, Chengdu Institute of Biology, Chinese Academy of Sciences (Voucher nos., SC1705, SC1706, and SC1707).…”
Section: Plant Extractionmentioning
confidence: 99%
“…Although oxidative stress is believed to be one of the primary contributors to the pathogenesis of osteoporosis via its role in osteoclastic resorption and detrimental effects on bone-forming osteoblasts (which could be prevented by supplementation with antioxidants (Arai et al, 2007;Chen et al, 2013;Muhammad et al, 2012;Rao and Rao, 2013), the detailed mechanism by which oxidative stress leads to osteoporosis through osteoclasts and osteoblasts remains controversial and unclear. Under these conditions, an imbalance between ROS production and antioxidant mechanisms may be disturbed, resulting in oxidative stress that could lead to osteoporosis (Abdollahi et al, 2005).…”
Section: Resultsmentioning
confidence: 99%